2019
DOI: 10.1038/s41598-019-41867-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered neural activity to monetary reward/loss processing in episodic migraine

Abstract: The dysfunctions of the mesolimbic cortical reward circuit have been proposed to contribute to migraine pain. Although supporting empirical evidence was mainly found in connection with primary rewards or in chronic migraine where the pain experience is (almost) constant. Our goal however was to investigate the neural correlates of secondary reward/loss anticipation and consumption using the monetary incentive delay task in 29 episodic migraine patients and 41 headache-free controls. Migraine patients showed de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 74 publications
2
9
0
Order By: Relevance
“… 4 Alongside these changes, studies point to abnormal reward processing in episodic migraine (EM) patients even during the interictal period, such as altered neural response to secondary (eg, monetary) reward/loss consumption. 5 Seemingly unrelated, it is evident that reward strongly interacts with pain through their overlapping neuroanatomical structures such as the amygdala and nucleus accumbens (NAc). 6 , 7 Chronic pain impairs the mesolimbic reward system, which leads to reduced motivated behaviors, negative affect, and further debilitating pain-related suffering.…”
Section: Introductionmentioning
confidence: 99%
“… 4 Alongside these changes, studies point to abnormal reward processing in episodic migraine (EM) patients even during the interictal period, such as altered neural response to secondary (eg, monetary) reward/loss consumption. 5 Seemingly unrelated, it is evident that reward strongly interacts with pain through their overlapping neuroanatomical structures such as the amygdala and nucleus accumbens (NAc). 6 , 7 Chronic pain impairs the mesolimbic reward system, which leads to reduced motivated behaviors, negative affect, and further debilitating pain-related suffering.…”
Section: Introductionmentioning
confidence: 99%
“…On average, 62 ± 36 participants (median 52 participants) were included per study. Of the identified studies, 68 studied groups with migraine without aura (2390), 15 migraine with aura (30,31,35,36,…”
Section: Resultsmentioning
confidence: 99%
“…However, we cannot exclude the possibility that migraine-related variables other than migraine frequency had an association with anticipatory processes. For instance, previous findings showed that monetary loss anticipation was associated with the time of the last attack [ 91 ]. In addition, migraine cycle can also alter pain processing.…”
Section: Discussionmentioning
confidence: 99%